Residual Hearing Preservation with the Evo® Cochlear Implant Electrode Array: Preliminary Results - Bento,Ricardo Ferreira (2016)
Abstract Introduction The preservation of residual hearing is currently an important challenge for cochlear implant surgeries. Indeed, if patients exhibit functional hearing after cochlear implantation, they can benefit from the combination of acoustical stimulation, usually in the low-frequencies and electrical stimulation in the high-frequencies. This combined mode of stimulation has proven to be beneficial both in terms of speech perception and of sound quality. Finding the right procedures for conducting softsurgeries and designing electrode arrays dedicated to hearing preservation is an open issue. Objective The objective of this study is to evaluate the combination of a soft-surgery procedure implicating round-window insertion and the use of dexamethasone and hyaluronic acid during surgery, with the use of a specifically designed straight soft electrode array, on hearing preservation in patients with functional hearing in the low frequencies. Methods This pre-clinical trial was conducted on seven patients with residual hearing in the low frequencies. The surgical method used employed a round window insertion and the use of topical dexamethasone. Results The soft-surgery protocol could be successfully followed in five patients. In this group, the average hearing threshold shift compared with pre-operative values was of 18.7 þ/ 16.1 dB HL up to 500 Hz and 15.7 þ/ 15.1 up to 1 kHz, demonstrating satisfying levels of hearing preservation. Conclusion We were able to demonstrate the possibility of preserving residual hearing in most of the patients using the EVO electrode. Significant residual hearing preservation levels were was obtained when a soft surgical approach involving round window insertion, dexamethasone and hyaluronic use during the surgery.